2018
DOI: 10.1007/s11469-018-9873-0
|View full text |Cite
|
Sign up to set email alerts
|

Internet Gaming Disorder Behaviors in Emergent Adulthood: a Pilot Study Examining the Interplay Between Anxiety and Family Cohesion

Abstract: Understanding risk and protective factors associated with Internet Gaming Disorder (IGD) has been highlighted as a research priority by the American Psychiatric Association, (2013). The present study focused on the potential IGD risk effect of anxiety and the buffering role of family cohesion on this association. A sample of emerging adults all of whom were massively multiplayer online (MMO) gamers (18-29 years) residing in Australia were assessed longitudinally (face-to-face: N = 61, M age = 23.02 years, SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 82 publications
6
70
0
4
Order By: Relevance
“…The present study provided findings indicating that gamers experiencing elevated symptoms of depression would report increased DG behaviors (H 1 ). This supports a substantial body of literature emphasizing the risk posited by symptoms of depression in developing addictive behaviors, particularly those of DG (Müller et al, 2015;Taymur et al, 2016;Burleigh et al, 2018;Adams et al, 2018;Liu et al, 2018;Stavropoulos et al, 2019b). More Specifically, gamers presenting with symptoms of depression may be at significantly higher risk of developing symptoms of DG than other gamers.…”
Section: Depression and Disordered Gaming Bondsupporting
confidence: 78%
See 3 more Smart Citations
“…The present study provided findings indicating that gamers experiencing elevated symptoms of depression would report increased DG behaviors (H 1 ). This supports a substantial body of literature emphasizing the risk posited by symptoms of depression in developing addictive behaviors, particularly those of DG (Müller et al, 2015;Taymur et al, 2016;Burleigh et al, 2018;Adams et al, 2018;Liu et al, 2018;Stavropoulos et al, 2019b). More Specifically, gamers presenting with symptoms of depression may be at significantly higher risk of developing symptoms of DG than other gamers.…”
Section: Depression and Disordered Gaming Bondsupporting
confidence: 78%
“…In addition to game genre and motivation, significant comorbidities have been supported between DG and other psychopathologies (Woelfling et al, 2008;Mihara & Higuchi, 2017;Pearcy et al, 2017;Kim et al, 2017;Adams et al, 2018;Liu et al, 2018), while addictions (such as DG) have been assumed to accommodate mood-regulation difficulties (Müller et al, 2015). In this context, depressive symptoms, including feelings of worthlessness, helplessness and hopelessness, difficulty concentrating, physical agitation (e.g., fidgeting), social isolation, and lethargic withdrawal from regular activities, have been strongly associated with addiction in general, and DG in particular (APA, 2013;Burleigh et al, 2018;Liu et al, 2018).…”
Section: Depression and Disordered Gamingmentioning
confidence: 99%
See 2 more Smart Citations
“…Family and parents play central roles in adolescents' socialization, behavioral development, and health [15]. Increasing studies have identified various family-related risk factors of IGD, including parental modelling of online gaming (e.g., parental gaming behavior [16] and parental attitudes [11]), poor parent-child relationship (e.g., perceived parental inconsistency [17], parental rejection [8], poor parental supervision [11,18]), poor family environment (e.g., poor family functioning [11], perceived family disharmony [6], and poor family cohesion [19]). Traditional Chinese culture and some Asian cultures emphasize parental psychological control (i.e., parental control that intrudes on the psychological and emotional development of the child) [20]; the attribute is a stressor and an interpersonal risk factor of adolescents' mental distress and behavioral problems [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%